Karakteristik Kimia Dan Sensori Selai Buah Naga Merah (Hylocereus polyrhizus) Dengan Penambahan Pektin - Mailoa, Meitycorfrida; Makuku, Viorenska; Palijama, Syane (Pattimura University Ambon Maluku Indonesia, 2024)
This study aims to determine the effect of adding pectin to the chemical and sensory characteristics of red dragon fruit (Hylocereus polyrhizus) jam. The study used a completely randomized design. One factor consists of 5 levels of pectin addition treatment, including control (without adding pectin), 1.5 g, 2 g, 2.5 g, and 3 g. The study concluded that adding pectin significantly affected water content, total sugar, vitamin C, pH, taste, texture, and overall. In contrast, it did not significantly affect the ash content and color of red dragon fruit jam. Red dragon fruit includes water content 37.88–57.63%, ash content 0.70–0.83%, total sugar 21.13–26.47%, vitamin C 0.0227–0.0324%, pH 4.2–4.5, and sensory properties such as color (somewhat like–like), taste (dislike–somewhat like), texture (dislike–like) and overall (somewhat like–like).